2014
DOI: 10.1016/j.nuclphysa.2014.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Search for double beta decay of 136Ce and 138Ce with HPGe gamma detector

Abstract: Search for double β decay of 136 Ce and 138 Ce was realized with 732 g of deeply purified cerium oxide sample measured over 1900 h with the help of an ultra-low background HPGe γ detector with a volume of 465 cm 3 at the STELLA facility of the Gran Sasso National Laboratories of the INFN (Italy). New improved half-life limits on double beta processes in the cerium isotopes were set at the level of lim T 1/2 ∼ 10 17 − 10 18 yr; many of them are even two orders of magnitude larger than the best previous results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…The remaining aqueous solution of ytterbium nitrate was acidified to pH ∼ 1 and purified by the liquid-liquid extraction technique. The liquidliquid extraction method has been proven to be the most effective technique for the purification of lanthanides from uranium and thorium traces [34,35,8]. A solution of 0.1 M tri-n-octylphosphine oxide (TOPO, 99%, Acros Organics) diluted in toluene (≤ 99.7%, ACS reagent, Sigma-Aldrich) has been used as non-polar organic phase for the extraction of U and Th from the polar aqueous solution.…”
Section: Elementmentioning
confidence: 99%
“…The remaining aqueous solution of ytterbium nitrate was acidified to pH ∼ 1 and purified by the liquid-liquid extraction technique. The liquidliquid extraction method has been proven to be the most effective technique for the purification of lanthanides from uranium and thorium traces [34,35,8]. A solution of 0.1 M tri-n-octylphosphine oxide (TOPO, 99%, Acros Organics) diluted in toluene (≤ 99.7%, ACS reagent, Sigma-Aldrich) has been used as non-polar organic phase for the extraction of U and Th from the polar aqueous solution.…”
Section: Elementmentioning
confidence: 99%
“…This process is expected to have a longer life-time and accompanied by a photon that carries away the decay energy. However, a possible enhancement of the capture rate by a factor as large as 10 6 can occur if the masses of the initial and final (excited) nucleus are degenerate [2], and hence this nuclear decay process is also attracting attention both theoretically [3,4,5,6] and experimentally [7,8,9,10,11]. Moreover, neutrinoless positron-emitting electron capture (0νβ + EC) and neutrinoless double beta plus decay (0νβ + β + ) may occur in the same nucleus depending on the mass difference between the initial and final nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…respectively, [62] are good candidates for 2β decay; competitive experimental results are reported in Ref. [156,157,64,158,159,160]. Moreover, the 142 Ce isotope can decay to the ground state of 138 Ba with emission of an α particle.…”
Section: Ce α Decaymentioning
confidence: 99%
“…Deviations from the theoretical shape could be used to limit (or to measure) the neutrino mass [256,257], however, taking into account the high T 1/2 and the low Q * β , such measurements will be extremely difficult. There are also other nuclides which are candidates for the lowest Q * β value in their decays to excited levels of daughter nuclei: 77 As, 79 Kr, 109 In, 111 In, 115 Cd, 131 I, 135 Cs, 146 Pm, 149 Gd, 155 Eu, 159 Dy, 161 Ho, 188 W, and 189 Ir [264,265,266,267] (see also the recent review [169] and an additional list of candidates in [268]); these decays are not observed yet and their Q β values are known currently with a low accuracy ( 1 keV or worse). Precise measurements of the atomic mass differences and possibly of the energies of the excited levels are needed in all these cases.…”
Section: CD β Decaymentioning
confidence: 99%